Phylogenetic studies on RoTat 1.2 VSG of Trypanosoma evansi isolate from semi arid India - DEVI, ANJALI; SHANKER, DAYA; SUDAN, VIKRANT; JAISWAL, AMIT; SINGH, AMIT; CHAUDHARY, MAHENDRA KUMAR (The Indian Journal of Animal Sciences, 2018)
RoTat 1.2 variant surface glycoprotein (VSG) is considered to be one of the most important VSGs expressed in many of the isolates of Trypanosoma evansi. This accounts for its utility as a potent molecule for both molecular and serological based detection of Surra. Of late, there are reports of its absence and variation from a fewer isolates of T. evansi. The study of these variations by means of molecular phylogenetic studies is of immense significance in determining the evolutionary phylogeny of these T. evansi isolates. With this information in the background, the present study was designed to clone and characterize RoTat 1.2 VSG from horse isolate of T. evansi from semi arid regions of India. There after, the gene was compared with various other isolates across the world. Interestingly, theisolate was found to be closer to camel isolates from Egypt than the other known isolates from India and Kenya. The finding is important from evolutionary point of view.